Expressive morphology in the languages of South Asia - Williams, Jeffrey P. (Jeffrey Payne), 1958- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
Expressive Morphology in the Languages of South Asia explores the intricacies of the grammars of several of the languages of the South Asian subcontinent. Specifically, the contributors to this volume examine grammatical resources for shaping elaborative, rhyming, and alliterative expressions, conveying the emotions, states, conditions and perceptions of speakers. These forms, often referred to expressives, remain relatively undocumented, until now. It is clear from the evidence on contextualized language use that the grammatically artistic usage of these forms enriches and enlivens both every day and ritualized genres of discourse. The contributors to this volume provide grammatical and sociolinguistic documentation through a typological introduction to the diversity of expressive forms in the languages of South Asia. This book is suitable for students and researchers in South Asian Languages, and language families of the following; Dravidian, Indo-Aryan, Iranian, Sino-Tibetan and Austro-Asiatic.
OCLC-licensed vendor bibliographic record.
Keywords: South Asia -- Languages -- Exclamations; South Asia -- Languages -- Morphology; South Asia -- Languages -- Semantics